Interest Rate Rules, Exchange Market Pressure, and Successful Exchange Rate Management - Franc Klaassen; Kostas Mavromatis (Tinbergen Institute, 2016)
Central banks with an exchange rate objective set the interest rate in response to what they call ''pressure.'' Instead, existing interest rate rules rely on the exchange rate minus its target. To stay closer to actual policy, we introduce a rule that uses exchange market pressure (EMP), the tendency of the currency to depreciate. Our rule can also explain a high interest rate even if the actual exchange rate is on target, in contrast to traditional rules. A further improvement is that the coefficient for EMP depends on the interest rate effectiveness: the rate should be used less if it is more effective. This shows how policy makers should adapt their policy in case of a structural change to avoid missing their objective. Our rule can be applied to many regimes, from the float to the fixed, and to many models, such as the New Keynesian model, as we illustrate.
Keywords: E43; E52; F31; F33; 330; DSGE; exchange market pressure; exchange rate regime; fixed exchange rate; monetary policy; open economy Taylor rule